2017
DOI: 10.1038/srep42550
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic pannexin 1 function is critical for neuropathic pain

Abstract: Neuropathic pain symptoms respond poorly to available therapeutics, with most treated patients reporting unrelieved pain and significant impairment in daily life. Here, we show that Pannexin 1 (Panx1) in hematopoietic cells is required for pain-like responses following nerve injury in mice, and a potential therapeutic target. Panx1 knockout mice (Panx1−/−) were protected from hypersensitivity in two sciatic nerve injury models. Bone marrow transplantation studies show that expression of functional Panx1 in hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 57 publications
(138 reference statements)
0
48
0
Order By: Relevance
“…Infiltration of MΦs into peripheral nerves and DRGs, as well as microglial activation in spinal cord, have been implicated in multiple inflammatory, neuropathic, and cancer pain conditions. MΦ/microglia-derived inflammatory mediators, growth factors, and spinal modulatory signaling have been suggested as the predominant modulatory factors for peripheral pain sensitization (15,(49)(50)(51)(52). It has been long understood that central sensitization of peripheral nerve injury responses, which serves as a pain signal amplification system in the CNS, is instrumental in the development of persistent neuropathic pain states (51).…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of MΦs into peripheral nerves and DRGs, as well as microglial activation in spinal cord, have been implicated in multiple inflammatory, neuropathic, and cancer pain conditions. MΦ/microglia-derived inflammatory mediators, growth factors, and spinal modulatory signaling have been suggested as the predominant modulatory factors for peripheral pain sensitization (15,(49)(50)(51)(52). It has been long understood that central sensitization of peripheral nerve injury responses, which serves as a pain signal amplification system in the CNS, is instrumental in the development of persistent neuropathic pain states (51).…”
Section: Discussionmentioning
confidence: 99%
“…Our present results do not exclude chemical communication that involves both neurons and SGCs. Indeed, we have shown that calcium waves in sensory ganglia are mediated by both these elements (Suadicani et al, ) and that Panx1 deletion or blockade provides pain relief (Hanstein et al, ; Weaver et al, ). Although the strength of coupling we have recorded between neurons and between SGCs and neurons is low, it could provide an important pathway for diffusional exchange of metabolites and signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for N‐G coupling was provided by imaging and electrophysiological studies of DRG in hindlimb pain studies (Kim et al, ) and by studies that have revealed dye spread between the cell types in both DRG and TG from several pain models (Spray & Hanani, ). Additional evidence for nonjunctional pathways includes the finding that the Pannexin 1 (Panx1) channels in SGCs release ATP and that allodynia is absent in Panx1 deficient mice (Hanstein, Hanani, Scemes, & Spray, ; Weaver et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Infiltration of MΦs into peripheral nerves and DRG, as well as microglial activation in spinal cord have been implicated in multiple inflammatory, neuropathic and cancer pain conditions. MΦ/microglia-derived inflammatory mediators, growth factors and spinal modulatory signaling have been suggested as the predominant modulatory factors for peripheral pain sensitization (35, 36). Recent findings in a rodent model of experimental trigeminal neuropathy suggest the involvement of MΦ infiltration at the site of nerve injury and increased oxidative stress leads to TRPA1 activation on trigeminal neurons, resulting in pain hypersensitivity (37).…”
Section: Discussionmentioning
confidence: 99%